Susceptor Packaging Material For Baking Flaky Pastry Dough In Microwave Oven - Main, Nor Mazlana (2008)
Microwave oven has been used extensively as to provide conveniences to consumers in preparing foods. The major problem in microwave baking is the inability of the microwave oven to induce browning on the surface of foods. To alleviate this problem and aid the browning and crisping on the surface of a baked food item, a packaging materials called susceptor has been developed specifically to support the usage of microwave oven. This study presents the design of susceptor packaging rigid box that is effective to bake flaky pastry dough (puff pastry) in microwave oven and performance evaluation of the product through microwave testing. Paperboard, corrugated board B-flute and metallized polyethylene terephthalate (MPET) film were used to design susceptor packaging rigid box. Testing on performance of susceptor packaging rigid box was implemented in microwave baking with different design and lamination of packaging material with puff pastry inside. Only one design of susceptor packaging rigid box was chosen which was design eight with the use of semi coating MPET film based on the desirable quality of the susceptor packaging rigid box and the puff pastry. Quality parameters of puff pastries such as temperature after baking, weight loss, colour changes at top and bottom surfaces, specific volume after baking and hardness were obtained as a result of the application on susceptor packaging rigid box through microwave testing. The sensory attributes of puff pastries such as appearance (colour), odour, taste, crispiness, texture (hardness) and overall acceptability were also examined using Hedonic Test acceptability of panelists on the puff pastries that were baked in susceptor packaging rigid box in microwave oven. As baking time was increased, all the quality parameters increased. Microwave baked puff pastries without susceptor packaging rigid box had some quality defects such as lack of colour, became soggy, shrank and brittle when cold. However, the microwave baked puff pastries had the highest specific volume and temperature. It was possible to improve the quality of microwave baked puff pastries with the aid of susceptor packaging rigid box. The colour of puff pastries changed into desirable rich brown and gave crispiness value similar to the conventionally baked ones at the three power levels used. However, microwave baked puff pastries with susceptor packaging rigid box had a lower volume at all power used. The best conditions for baking puff pastries in microwave oven with susceptor packaging were 270s, 285s and 300s at 340W microwave power; 165s and 180s at 500W microwave power; and 105s and 120s at 790W microwave power. When susceptor packaging was applied for this condition, it reduced conventionally baking time about 75%-91%. Results of sensory evaluation showed that puff pastries baked in conventional oven were highly accepted by the panelists with mean scores of 7.67 (mean scale: 1-9). The results followed by puff pastries that were baked with susceptor packaging rigid box with the mean score value of 6.93. Microwave baked puff pastries had the lowest mean score in overall acceptability (4.47).